The potential and obstacles of Malaysia’s Halal Certification towards global halal standard - Ghazali, Mohd Al'Ikhsan; Md Sawari, Siti Salwa; Awang, Mohd. Daud; Jusoh, Mohd Kamal Azman (Rynnye Lyan Resources, 2023)
The frailty to produce a global halal standard has become one of the reasons why the halal industry cannot grow faster, despite increased demand for halal products around the world. Moreover, the industry welcomes the idea of creating a global halal standard. Numerous sectors including inter governmental agencies and small businesses have recognised the necessity for a global halal standard recognised by all trade in countries. The methodology used in this article is qualitative, which involves secondary analysis with reference to academic materials to describe the potential and challenges of halal standard. In response to this demand and awareness, this article assessed the potential of the Malaysian Halal Standard to be accepted globally. The finding in this article has highlighted the halal industry has become one of the fastest-growing economies, and Malaysia has the potential to be a global hub for the halal food industry. Secondly, Malaysia’s halal standard has been accepted at the international level and is the leading halal standard among Islamic countries.